1999
DOI: 10.1080/096374899101076
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive value of various breads in Saudi Arabia

Abstract: The nutritive value of nine Saudi breads prepared from wheat, millet and corn were measured chemically by proximate, minerals and vitamins analyses. On fresh weight basis, the bread contained 26.4-44.7% moisture, 6.6-10.4% protein, 0.4-2.4% fat, 40.2-60.6% available carbohydrates, 1.8-5.7% dietary fibre, 0.6-2.4% ash and 190-273 Kcal (metabolizable) per 100 g. All the breads were low in Ca (2.2-12.5 mg/100 g), P ranged from 41.9-320.8, Na 83.2-794.6, K 0.7-224.2 and Fe 1.6-7.8 mg/100 g. The contents of vitamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
3
7
1
Order By: Relevance
“…The mineral composition data (Table 2) showed that, sodium content in all kinds of bread ranged from 58.16-555.6 mg/100 g. Mulwah with 10% of bran content (C2) contain the higher quantity of Na which may not be suitable for hypertensive individuals. Similar results in breads made of white wheat flour with sodium content of 217 mg/100 g, 548 mg/100 g and content of 207-304 mg/100 g respectively as reported 6,7,9 . Bread with reduced sodium has been marketed helps to maintain a healthy heart and circulation 19 .…”
Section: Fatsupporting
confidence: 84%
See 3 more Smart Citations
“…The mineral composition data (Table 2) showed that, sodium content in all kinds of bread ranged from 58.16-555.6 mg/100 g. Mulwah with 10% of bran content (C2) contain the higher quantity of Na which may not be suitable for hypertensive individuals. Similar results in breads made of white wheat flour with sodium content of 217 mg/100 g, 548 mg/100 g and content of 207-304 mg/100 g respectively as reported 6,7,9 . Bread with reduced sodium has been marketed helps to maintain a healthy heart and circulation 19 .…”
Section: Fatsupporting
confidence: 84%
“…The results shows that (Table 1), the protein content in the breads (A2,B2) made of brown flour (Extraction rate 85-95%) differ significantly in this nutrient with all other bread kinds except with that public flat bread (Mulawah) which contain 10% wheat bran in it's dough that increase it's protein content. Though the protein content of all kinds of Yemeni bread under study are high comparatively with the same kind of Saudi breads reported by Al-kanhal et al 9 but approximately with the same content of protein of balady and pan breads reported by Alian et al 5 & Hussein et al 6 , consumed in Egypt. After all the protein content of flat bread (Mufroud) prepared from brown wheat flour should contain protein content not less than 12% as well as pan and sliced bread should contain protein content not less than 11% according to Yemeni standards of bread (specification No.2001/160) such status clarify that the protein content of imported wheat grain are originally with low content, since with the addition of 10% wheat bran to white wheat flour could not provide the bread it's protein content to fulfill the condition of local specification.…”
Section: Proteinsupporting
confidence: 59%
See 2 more Smart Citations
“…Its price is affordable and it has high protein content driven from "Ful" and high carbohydrate from "Tamees'. This wheat bread (355 g/head/day) provided 45 and 61% of energy and protein requirements respectively at national level per person per day [24,25]. Nutritional evaluation of some legume-based dishes consumed in Saudi Arabia was already studied by al-Kanhal et al who indicated that legume-based dishes which include "Ful" contributed to 13% -25%, 15% -64% and 16% -60% of the total food energy from protein, fat and carbohydrates respectively.…”
Section: Discussionmentioning
confidence: 99%